Bacteriological Finding in Chronic Suppurative Otitis Media and Antibiotic Sensitivity (Medico Legal Update, 2020)
Background: Chronic Suppurative Otitis Media(CSOM) is one of the most common infection and a majorhealth problem in developing countries leads to serious complications if not treated properly.Objective: The aim of this study is to identify the most common bacterial isolates causing CSOM in oursetup to help guide the effective management of the disease. Its poor response to routine treatment andemergence of resistance strains were the factors responsible for undertaking this studyMaterials and Method: Total 88 patients were included in the study with unilateral or bilateral dischargefor more than 3 months at ending ear nose throat(ENT) outpatient department, AL-Hussein teaching hospitalin AL-Samawa city from July 2018 to December 2018 . Samples were taken by using sterile swabs andwere cultured on aerobic media and their drug susceptibility was tested by using Kirby Bauer disc diffusionmethod.Results: Overall microbiology of 88 samples was studied. Pseudomonas aeruginosa (32.95%) was the mostcommon bacterial isolate, followed by staphylococcus (30.86%), Proteus mirabilis (15%), E coli (7.95%),streptococcus pyogen (4.54%) klebsiella sp and acinoccocus sp (2.27%) enterococcus sp (3.27%).Conclusion: Knowledge of the local bacteriological pattern and their antibiotic sensitivity is essential forthe early, effective and cost saving treatment of CSOM and to prevent the complications and developmentof antibiotic resistance.